Analysis of Internal Control System in Employee Payrolling Procedures at PT. Great Dumping - Rosdiyati (Jurnal Mantik, 2020)
Companies have a good chance to survive and advance if they have the right employees, so it requires effort to find, select, and train candidates or employees. Conversely, employees need the company as a place to make a living. Employees must work to make ends meet. Therefore, employees are entitled to a salary that is in accordance with their quality. The salary received by employees should be a reasonable salary. Based on the results of research and discussion, the authors can conclude several things in the internal control system in the employee payroll procedures at the ES BATU Dumpi Agung Lamongan FACTORY are: In the organizational structure that clearly separates its functional responsibilities, the ES BATU Dumpi Agung Lamongan FACTORY has not implemented a separation of functions strictly because there is still a dual function between the present time recording section and the operations section. The distribution of salaries to each production employee whose payment method was submitted through the foreman was deemed inaccurate because it was not in accordance with their duties. In the system of authority, authorization and recording procedures, ES BATU Dumpi Agung Lamongan FACTORY has implemented it well. All employee names listed on the payroll have a SK (Decree) authorized by the Director. And in healthy work practices in carrying out the duties and functions of each organizational unit, the Dumpi Agung Lamongan ES BATU FACTORY has done it well.